Comparative Evaluation of the Chemical Composition, Antioxidant and Antimicrobial Activities of the Volatile Oils of Hawk Tea from Six Botanical Origins. Issue 11 (4th November 2016) - Yu, Bao; Zhang, Dan; Yan, Xue‐Wei; Wang, Jian‐Wei; Yao, Ling; Tan, Li‐Hong; Zhao, Sheng‐Ping; Li, Na; Cao, Wei‐Guo
Abstract : In this study, volatile oils of six Hawk tea varieties were studied for their chemical composition, antioxidant and antimicrobial activities to screen the most suitable botanical origins of Hawk tea. A total of 72 components were separated and identified from the six oils. The major constituents of the volatile oils were: α ‐pinene, camphene, limonene, 1, 8‐cineole, linalool, cis ‐nerolidol, and germacrene B. Moreover, the volatile oils were evaluated for antioxidant potential and antimicrobial activities. The results showed that all volatile oils exhibited acceptable antioxidant and antimicrobial activities, which suggested that these volatile oils may serve as natural alternatives to synthetic antioxidants and preservatives to be applied in food and pharmaceutical industries. Principal component analysis results denoted that some major compounds may be closely related to the antioxidant and antimicrobial activities. It also showed that the volatile oils from Litsea coreana var. lanuginosa and Litsea pungens Hemsl . were characterized by positive values of first two principal components, indicating higher active chemical compounds and antioxidant and antimicrobial activities compared with other species. Thus, they were temporarily considered as good sources of Hawk tea. Abstract :